Cross-Cultural Communication Understanding in Business and Economics ESP Teaching - Pratiwi, Berlin (English Education and Literature Journal (E-Jou), 2022)
Language teaching should have portions for cultural reviews and studies that are relevant to the topics and learners’ needs. This research was qualitative descriptive aimed to describe the cross-cultural understanding implementation in business and economic ESP class. It is significant to describe the class realization toward cultural aspect understanding since the findings are expected to enhance future class preparation. Better cultural-based-prepared material is believed to bring a better social impact on learners. Lecturers’ and students’ perspectives based on several interviews were the basis for final finding construction. Three English lecturers were involved. Snowball sampling was the sampling method employed resulting in 40 students involved in interviews. In the context of business and economics ESP in Universitas Putra Bangsa, lecturers provided material related to cross-cultural understanding in verbal realization i.e. in the level of words, phrases, clauses, and sentences. The above levels were introduced by the lecturers with cultural and contextual approaches. Students expected more strategic-applicable utterances for daily communication in a workplace setting. Lecturers delivered the general importance of non-verbal cross-cultural understanding in the form of kinesics (eye contact and gesture), proxemics, and artifactual in a workplace setting. Kinesics was prominent, while proxemics and artifactual were least prepared. Students found practical activities in non-verbal cross-cultural understanding realization were interesting and challenging. Keywords: communication; cross-cultural understanding; English for specific purposes